Le recours subrogatoire de l’assureur - LeMay, Jacques; Ouellet, Claude (Assurances)

(untitled) (HEC Montréal, 1990)
Subrogation is a right which is not only stipulated in insurance policies, but also legally promulgated by law (Article 2576 C.C.) According to the authors, Jacques LeMay and Claude Ouellet, the doctrine of subrogation causes little difficulty in practice. However, they comment on potential problems that Canadian courts have recognized, namely: the principle of legal subrogation, without the consent of the Insured, where the right to pursue is transferred to the Insurer; its limitation to the indemnity actually paid by the Insurer; the situation where the Insurer has no obligation to pay in respect of the insurance policy.